Spin-current-mediated rapid magnon localisation and coalescence after ultrafast optical pumping of ferrimagnetic alloys - E. Iacocca (Nature Portfolio, 2019)
The understanding of the magnetisation evolution upon femtosecond optical pumping remains elusive. The authors perform resonant X-ray magnetic scattering measurements and multiscale simulations that reveal rapid magnetic order recovery in ferrimagnets via nonlinear magnon processes.